2021
DOI: 10.1016/j.dental.2020.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior of endodontically treated premolars restored with different fiber-reinforced designs

Abstract: Objectives. The aim was to investigate the fatigue survival and marginal-gap inside the rootcanal of endodontically treated (ET) premolars reinforced by various fiber-reinforced postcore composites (FRCs). Moreover, composite-curing at different depths in the canal was evaluated.Methods. 170 intact upper-premolars were collected and randomly divided into ten groups (n = 15). One group served as control (intact-teeth). After endodontic procedure standard MO cavities were prepared and restored with different pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 59 publications
(78 reference statements)
2
35
0
1
Order By: Relevance
“…This is due to the obvious difference in fracture toughness between reinforced and non-reinforced composites. Previous studies have shown that fiber-reinforced composites have the ability to re-direct and stop crack propagation within the materials [ 13 , 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to the obvious difference in fracture toughness between reinforced and non-reinforced composites. Previous studies have shown that fiber-reinforced composites have the ability to re-direct and stop crack propagation within the materials [ 13 , 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another major difference between the packable and flowable SFRC is that the flowable one contains 25 wt% of fibers, while in the packable variant this ratio is only 9 wt%. So far, flowable SFRC has yielded promising results when utilized in direct restorations in different clinical situations [ 16 , 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach, also called the individual fiber post concept, has been used successfully with continuous long glass fibers [ 23 , 24 ]. On the other hand, fiber-reinforced core composites showed the ability to re-direct and stop crack propagation within the materials [ 25 ]. The presence of such energy-absorbing and stress-distributing fibers allows crack propagation to be deflected away from the bulk of the material and toward the peripheries [ 22 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%